Evaluation of Crest Guideline Validity for Diagnosis of Non-Facial Cellulites - Mohsen, Abbasi; Samaneh, Abiri; Mohammad-Javad, Ghanbari; Maryam, Hashemi Orimi (Journal of Dermatologic Research And Therapy, 2016)
Cellulitis is an acute, spreading pyogenic inflammation of the dermis and subcutaneous tissue, usually complicating a wound, ulcer, or dermatosis. Inappropriate diagnosis of cellulitis is a problem and would need prospective rather than retrospective studies to quantify the extent. There is one national guideline for the management of patients with cellulitis. The aim of this study is to determine the validity of Crest guideline in the patients with non-facial cellulitis. This prospective cohort study was conducted on all Adult patients with cellulites who were admitted at Resole-Akram and Sina emergency department between November 2013 and January 2014. Based on admission duration, the patients were randomly divided into two groups including primary and secondary outcome, <24-hours or >24-hours admission, respectively. Out of 89 admitted patients, 55% were hospitalized over 24 hours and 20% of them had significant systemic symptoms. The most patients (n= 42) had either systemically ill or systemically well or class II followed by classes I (n=28), III (n=18), and IV (n=1). There was significant relevancy between age, fever, PR, infected organ, leukocytosis, diabetes mellitus, IUDA, human bite, and primary outcome. In conclusion, factors associated with admission were age, presence of multiple comorbid conditions, diabetes mellitus, human bite, IUDA, infected organ, leukocytosis and fever. These results showed that the decision in the emergency department was mostly the same as Crest guideline and the prospection of admission and discharge of these patients was almost according to the educations of Crest guideline.
Keywords: cellulites; department of emergency; Crest Guideline; hospitalization; discharge